The Effect Of Ginger Warm Water Foot Soak Therapy On Blood Pressure Reduction In Elderly Patients - Salsabilla Puteri Ifayarta; Chairul Huda Al Husna (Jurnal Ilmiah Multidisiplin, 2025)
Hypertension is one of the main health problems in the elderly with an increasing and often uncontrolled prevalence. This condition can trigger serious complications such as stroke, heart disease, and impaired function of other organs, so proper management is needed. In addition to pharmacological therapies, nonpharmacological interventions such as hydrotherapy and complementary herbs are beginning to be considered as alternatives to help lower blood pressure. This study aims to evaluate the therapeutic effect of soaking feet in warm water with ginger on changes in blood pressure in the elderly with hypertension. The study used a case report design with two elderly respondents with hypertension, conducted for seven consecutive days in September 2025. Blood pressure was measured before and after daily therapy, then analyzed descriptively in the form of individual blood pressure changes. The results showed a decrease in blood pressure in both respondents after the intervention. In the first responder, the initial systolic blood pressure of 178 mmHg changed to 160 mmHg on day 5, and diastolic blood pressure from 96 mmHg to 98 mmHg after the last day of intervention, with fluctuations decreasing after each therapy session. In the second respondent, the initial systolic blood pressure of 166 mmHg decreased to 152 mmHg on day 5, while diastolic pressure dropped from 101 mmHg to 98 mmHg. These results show that ginger warm water foot soaking therapy has the potential to have an effect in lowering blood pressure in the elderly with hypertension.